(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Early childhood development is a sensitive period in which cognitive, language, motor, and socio-emotional skills rapidly emerge and shape later school readiness, health, and participation. In primary care, clinicians see most children repeatedly through well-child visits, making this setting ideal for early identification of developmental delays and timely referral to early intervention services. This article reviews a practical primary-care methodology for early detection in children under five, emphasizing the complementary roles of developmental surveillance and standardized screening. It summarizes when to screen, how to select tools, and how to interpret results, with a focus on implementation steps that are feasible in busy clinics, including parent-completed questionnaires, brief autism-specific instruments, and structured follow-up pathways. Evidence-informed approaches to communication with families, documentation, referral, and quality improvement are outlined. The article argues that the benefit of screening depends not only on tool accuracy, but also on workflow integration, clinician training, family engagement, and reliable access to evaluation and early intervention.